A lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating and a preparation method thereof
By forming a heterostructured nanocomposite phosphate carbon-containing coating on the inner core surface of the lithium-rich manganese-based positive electrode material, and adding a composite coating of metal sulfide and metal boride to the outer layer, the insufficient performance problems of lithium-rich manganese-based positive electrode material in the application of lithium-ion batteries are solved, and its electrochemical performance and cyclic stability are significantly improved.
Patent Information
- Application Number
- CN202411945366.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
In practical applications, lithium-rich manganese-based positive electrode materials face the problems of low efficiency, poor rate performance, voltage attenuation and voltage hysteresis, poor oxygen release and circulation performance of the meter interface, which limits its application in lithium-ion batteries.
The lithium-rich manganese-based positive electrode material is coated with a lithium-rich manganese-based core material. The surface of the lithium-rich manganese-based core material is covered with a nanocomposite phosphate carbon-containing cladding layer. The contact interface between the cladding layer and the core is a spinel-like structure, and the remaining part is an olivine-type structure, and a composite cladding layer of metal sulfide and metal boride is added to the outer layer.
Through the formation of heterostructure, the electrochemical performance and cyclic stability of the material are improved, the first Coulomb efficiency and rate performance are improved, the loss of irreversible lithium sources is reduced, and the structural stability and electrical conductivity of the material are enhanced.
Smart Images

Figure BDA0005213517440000131 
Figure HDA0005213517450000011 
Figure HDA0005213517450000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery positive electrode materials, and specifically relates to a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating and a preparation method thereof. Background Art
[0002] As the global demand for sustainable energy solutions grows, lithium-ion batteries are increasingly being used in a wide range of applications, from electric vehicles to energy storage devices for renewable energy systems. In order to meet the market demand for higher energy density, longer life and lower cost batteries, researchers are constantly exploring new battery materials and technologies, striving to break through the limitations of existing technologies. In this context, lithium-rich manganese-based cathode materials have become a research hotspot due to their unique properties.
[0003] Lithium-rich manganese-based cathode materials (usually referred to as Li 1+x Mn 1-x O2, where x≤0.5) is a cathode material with a high theoretical specific capacity (up to 250 mAh / g or more), which is much higher than the currently widely used ternary materials (about 220 mAh / g) and lithium iron phosphate (about 150 mAh / g). In addition to high specific capacity, lithium-rich manganese-based materials also have high operating voltages and relatively low preparation costs, making them ideal candidates for the next generation of lithium-ion battery cathode materials.
[0004] However, despite the great potential shown by lithium-rich manganese-based cathode materials, they still face many challenges in practical applications, which are mainly reflected in the following aspects: Low first coulombic efficiency: During the first charge and discharge process, due to the changes in the internal structure of the material and the decomposition of the electrolyte, the irreversible capacity loss is large, and the first coulombic efficiency is usually less than 80%. Poor rate performance: At high current density, the ion diffusion rate and electron transmission capacity of the material are insufficient, which affects the fast charging capability and power output of the battery. Voltage decay and voltage hysteresis: After a long period of cycling, the operating voltage of the battery will gradually decrease, and at the same time, there will be obvious voltage hysteresis during the charge and discharge process, which limits the energy utilization efficiency of the battery. Surface oxygen release: Under high voltage, oxygen is easily released from the surface of the cathode material, which not only reduces the safety and stability of the battery, but also may trigger other negative chemical reactions. Poor cycle performance: As the number of charge and discharge times increases, the material structure gradually degrades, resulting in a decrease in capacity retention, affecting the service life of the battery.
[0005] At present, the preparation method of lithium-rich manganese-based positive electrode materials usually uses conventional calcination combined with surface coating, which has problems such as poor rate performance, low first efficiency, and poor cycle performance. Although the conventional first efficiency improvement scheme can improve the first efficiency of the material by constructing anion and cation defects at the surface interface, it will deteriorate the cycle performance of the material. The conventional doping scheme is used to improve the rate performance of the material, but it usually also significantly reduces the initial capacity of the material.
[0006] These problems seriously hinder the commercial application of lithium-rich manganese-based materials, and researchers need to continue to study and innovate technology to solve them. Summary of the invention
[0007] In view of the problems in the prior art, the present invention discloses a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating and a preparation method thereof; the positive electrode material of the present invention is coated with a nano-composite phosphate carbon-containing coating layer on the surface of a lithium-rich manganese-based core material; the contact interface between the nano-composite phosphate carbon-containing coating layer and the core is a spinel-type structure, and the remaining part is an olivine-type structure; the presence of the heterogeneous structure helps to improve the electrochemical performance and cycle stability of the material during battery application.
[0008] The present invention is achieved through the following technical solutions:
[0009] In the first aspect, the present invention provides a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating, wherein the chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)Li 1-y Q y TMO2@A / C@N;
[0010] Among them, xLi2MnO3·(1-x)Li 1-y Q y TMO2 is a doped lithium-rich manganese-based core; 0<x<0.5, 0<y<0.1, Q is one or more alkali metal elements or alkaline earth metal elements, TM is a transition metal element, A / C is a nanocomposite phosphate carbon-containing coating layer coated outside the core, A is a nanocomposite phosphate (LiG a (PO4) b ), G is a metal element of a multivalent metal ion, and C is a carbon material; N is a composite coating layer coated outside the nano-composite phosphate carbon-containing coating layer, and the composite coating layer contains metal sulfide and metal boride: wherein the contact interface between the nano-composite phosphate carbon-containing coating layer and the inner core is a spinel-type structure, and the remaining part is an olivine-type structure.
[0011] As a further solution, in Q, the alkali metal element is selected from sodium and potassium; and the alkaline earth metal element is selected from magnesium.
[0012] As a further solution, the ratio of the Q mass to the total mass of the lithium-rich manganese-based positive electrode material is 0.01-0.3%.
[0013] As a further embodiment, the nanocomposite phosphate (LiG a (PO4) b ), the mass of phosphate accounts for 0.7% to 1.5% of the total mass of the lithium-rich manganese-based positive electrode material.
[0014] As a further solution, in the lithium-rich manganese-based positive electrode material compositely coated on the surface of the heterostructure, the molar ratio of phosphate to lithium is in the range of: PO4:Li=1:(0.6-1.3).
[0015] The present invention does not specifically limit the ratio of the mass of multivalent metal ions to the total mass of the lithium-rich manganese-based positive electrode material. Those skilled in the art can make corresponding adjustments according to the corresponding molar amount of phosphate when selecting different types of multivalent metal phosphates as needed.
[0016] As a further solution, the carbon content in the nano-composite phosphate carbon-containing coating layer accounts for 0.1-0.3% of the total mass of the lithium-rich manganese-based positive electrode material.
[0017] As a further solution, the added amount of the composite coating layer of metal sulfide and metal boride accounts for 0.01-0.5% of the total mass of the lithium-rich manganese-based positive electrode material.
[0018] Furthermore, the stoichiometric ratio of the metal sulfide to the metal boride is selected from 1:(0.5-2).
[0019] As a further embodiment, the transition metal element is selected from one or more of iron, cobalt, manganese or nickel.
[0020] As a further solution, the raw materials of the nanocomposite phosphate carbon-containing coating layer include multivalent metal ion phosphate, a lithium source, and an organic carbon source.
[0021] As a further embodiment, the polyvalent metal ion is selected from Cu 2+ , Fe 2+ 、Co 2+ , Pb 2+ 、Zn 2+ , Mn 2+ 、Ni 2+ 、Al 3 + 、Ti 4+ or V 3+ One or more of .
[0022] Furthermore, the polyvalent metal ion is preferably selected from Fe 2+.
[0023] As a further embodiment, the multivalent metal ion phosphate is selected from one or more of FePO4, Zn3(PO4)2, AlPO4, and Ti3(PO4)4.
[0024] Furthermore, the multivalent metal ion phosphate is preferably selected from FePO4.
[0025] As a further embodiment, the organic carbon source includes one or more of organic acids, sugars, and lipids.
[0026] Furthermore, the organic acid includes one or more of formic acid, acetic acid, propionic acid, lactic acid, butyric acid, acetic acid, oxalic acid, and citric acid.
[0027] Furthermore, the carbohydrate substance includes one or more of glucose, fructose, sucrose and maltose.
[0028] Furthermore, the lipid substances include one or more of fatty acids, triglycerides, phospholipids, and cholesterol.
[0029] As a further embodiment, the metal sulfide is selected from one or more of molybdenum sulfide, antimony sulfide and zirconium sulfide.
[0030] As a further embodiment, the metal boride is selected from one or more of titanium diboride and zirconium diboride.
[0031] In a second aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating, which is used to prepare the lithium-rich manganese-based positive electrode material described in the first aspect; the preparation method comprises the following steps performed in sequence: according to the stoichiometric ratio:
[0032] S1: Weighing a lithium-rich manganese-based precursor material, a lithium source, and a Q source, mixing them evenly, and then pre-sintering at a low temperature to obtain a doped lithium-rich manganese-based core material;
[0033] S2: Weigh a multivalent metal ion phosphate, a lithium source, an organic carbon source, and the doped lithium-rich manganese-based core material described in S1, mix them evenly, and perform a second sintering to obtain a lithium-rich manganese-based positive electrode material coated with a heterostructure surface;
[0034] S3: The lithium-rich manganese-based positive electrode material coated on the surface of the heterostructure described in S2 is evenly mixed with metal sulfide and metal boride, and subjected to a third sintering treatment to obtain a lithium-rich manganese-based positive electrode material compositely coated on the surface of the heterostructure.
[0035] As a further solution, the added molar amount of the lithium source in S2 is the molar amount of the phosphate group of the multivalent metal ion phosphate in S2 minus (0.08-0.12)*the mass of the doped lithium-rich manganese-based core material in S1.
[0036] As a further embodiment, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium nitrate.
[0037] As a further solution, the lithium-rich manganese-based precursor material includes Ni a Co b Mn c (OH)2 and Ni a Co b Mn c CO3, wherein 0.28≤a≤0.42, 0≤b≤0.2, 0.6≤c≤0.7, a+b+c=1.
[0038] As a further embodiment, the Q source is selected from one or more of sodium carbonate, sodium hydroxide, sodium peroxide, sodium fluoride, magnesium fluoride, magnesium carbonate, magnesium hydroxide, and potassium carbonate.
[0039] As a further embodiment, the particle size of the multivalent metal ion phosphate is between 20 nm and 100 nm.
[0040] As a further solution, the low-temperature pre-sintering temperature is selected from 500 to 800° C., and the low-temperature pre-sintering time is selected from 1 to 5 hours.
[0041] As a further solution, the second sintering temperature is selected from 750° C. to 950° C., and the second sintering time is selected from 10 to 15 hours.
[0042] As a further solution, the third sintering temperature is selected from 400 to 600° C., and the third sintering time is selected from 5 to 8 hours.
[0043] In the preparation method of the present invention, those skilled in the art can feed materials according to the stoichiometric ratio, that is, according to the proportional relationship between the elements of the lithium-rich manganese-based positive electrode material, and determine the corresponding stoichiometric ratio taking into account the losses during the feeding and preparation process.
[0044] In the third aspect, the present invention provides a lithium-manganese-rich positive electrode material with a heterogeneous structure surface composite coating as described in the first aspect, or a lithium-manganese-rich positive electrode plate, an electrode assembly, a battery cell, and an energy storage device with a heterogeneous structure surface composite coating obtained by the preparation method described in the second aspect.
[0045] The characteristics and beneficial effects of the present invention are:
[0046] (1) In the positive electrode material provided by the present invention, the contact interface between the lithium-rich manganese-based core material and the nanocomposite phosphate carbon-containing coating layer has a unique spinel-like heterogeneous structure; at the same time, the part of the nanocomposite phosphate carbon-containing coating layer that is not in contact with the core interface has an olivine-type structure; forming a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating. The presence of the spinel-like structure helps to form a three-dimensional Li diffusion channel; improves Li transmission efficiency and reduces the loss of irreversible lithium sources; and the presence of the spinel-like heterogeneous structure is conducive to improving the stability of the interface between the coating layer and the core material, reducing the interface resistance, thereby improving the cycle stability and rate performance of the battery.
[0047] (2) The present invention uses an organic carbon source when preparing the nano-composite phosphate carbon-containing coating layer; on the one hand, when the organic carbon source is used for reduction reaction and decomposition, it is an exothermic reaction, which to a certain extent helps to construct oxygen vacancies on the surface of the lithium-rich manganese-based material, improve the surface activity of the lithium-rich manganese-based core material, accelerate the mass transfer process, enhance the kinetic properties of the material, and promote the formation of a spinel-like heterostructure; on the other hand, the carbon material of the decomposition product of the organic carbon source can be evenly distributed on the surface of the lithium-rich manganese-based core material to form a carbon layer with good conductivity.
[0048] (3) The present invention further adds a composite coating layer of metal sulfide and metal boride to the outermost layer of the positive electrode material; the presence of the coating layer helps to play an insulating role, improve the interface stability of the material, effectively inhibit the occurrence of side reactions between the electrolyte and the positive electrode active material, avoid increasing the impedance of the interface, and effectively improve the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 It is the Raman spectrum test graph of Example 1 and Comparative Example 2;
[0051] Figure 2 It is a cycle test diagram of the positive electrode materials of Example 1 of the present invention and Comparative Example 5;
[0052] Figure 3 It is a rate test diagram of the positive electrode materials of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0053] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0054] In the first aspect, the present invention provides a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating, wherein the chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)Li 1-y Q y TMO2@A / C@N;
[0055] Among them, xLi2MnO3·(1-x)Li 1-y Q y TMO2 is a doped lithium-rich manganese-based core; 0<x<0.5, 0<y<0.1, Q is one or more alkali metal elements or alkaline earth metal elements, TM is a transition metal element; A / C is a nanocomposite phosphate carbon-containing coating layer coated outside the core, A is a nanocomposite phosphate (LiG a (PO4) b ), G is a metal element of a multivalent metal ion, and C is a carbon material; N is a composite coating layer coated outside the nano-composite phosphate carbon-containing coating layer, and the composite coating layer contains metal sulfide and metal boride; wherein the contact interface between the nano-composite phosphate carbon-containing coating layer and the inner core is a spinel-type structure, and the remaining part is an olivine-type structure.
[0056] The lithium-rich manganese-based positive electrode material provided by the present invention has a unique spinel-like heterogeneous structure at the contact interface between its lithium-rich manganese-based core material and the nano-composite phosphate carbon-containing coating layer; at the same time, the nano-composite phosphate carbon-containing coating layer has an olivine-type structure at the part that is not in contact with the core interface; a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating is formed. The existence of the spinel-like heterogeneous structure is conducive to improving the stability of the interface between the coating layer and the core material, reducing the interface resistance, thereby improving the cycle stability and rate performance of the battery; at the same time, the spinel-like heterogeneous structure has a three-dimensional Li diffusion channel, and the surface modification of the spinel-like nanoparticles can improve the Li transmission efficiency and reduce the loss of irreversible lithium source, thereby improving the specific capacity and coulomb efficiency.
[0057] During the high-temperature sintering preparation process of the nano-composite phosphate lithium-rich material adopted by the present invention, the phosphate will undergo mass transfer with the outer surface of the lithium-rich core material to form a spinel-like heterogeneous structure layer; during the phosphate composite sintering process, the organic carbon source used in the present invention can, on the one hand, construct oxygen vacancies on the surface of the lithium-rich manganese-based material during the decomposition process, effectively reduce the oxygen release reaction on the surface of the material, increase the surface activity of the lithium-rich manganese-based core material, and enhance the kinetic properties of the material; at the same time, the decomposition of the organic carbon source is an exothermic reaction, which can accelerate the mass transfer process and promote the formation of the spinel-like heterogeneous structure; on the other hand, the carbon material of the decomposition product of the organic carbon source can be evenly distributed on the surface of the lithium-rich manganese-based core material to form a carbon layer with good conductivity; this helps to improve the conductivity, rate performance and cycle performance of the lithium-rich manganese-based positive electrode material in battery charging and discharging applications.
[0058] Moreover, the portion of the nano-composite phosphate carbon-containing coating layer that is not in contact with the lithium-rich manganese-based core material has an olivine structure, and the olivine structure is more stable than the layered structure, which is beneficial to improving the structural stability of the material. In addition, the lithium-rich manganese-based positive electrode material of the present invention also includes a composite coating layer of metal sulfide and metal boride. The presence of the coating layer can improve the interface stability of the material, isolate the inner coating layer from the electrolyte, inhibit side reactions on the surface of the electrolyte and the lithium-rich positive electrode material, improve the cycle performance of the material, reduce the loss of the electrolyte and the generation of by-products, and improve the cycle stability.
[0059] As a further solution, in Q, the alkali metal element is selected from sodium and potassium; and the alkaline earth metal element is selected from magnesium.
[0060] As a further solution, the ratio of the Q mass to the total mass of the lithium-rich manganese-based positive electrode material is 0.01-0.3%.
[0061] As a further embodiment, the nanocomposite phosphate (LiG a (PO4) b ), the mass of phosphate accounts for 0.7% to 1.5% of the total mass of the lithium-rich manganese-based positive electrode material.
[0062] As a further solution, in the lithium-rich manganese-based positive electrode material compositely coated on the surface of the heterostructure, the molar ratio of phosphate to lithium is in the range of: PO4:Li=1:(0.6-1.3).
[0063] The present invention does not specifically limit the ratio of the mass of multivalent metal ions to the total mass of the lithium-rich manganese-based positive electrode material. Those skilled in the art can make corresponding adjustments according to the corresponding phosphate addition amount when selecting different types of multivalent metal phosphates as needed.
[0064] As a further solution, the carbon content in the nano-composite phosphate carbon-containing coating layer accounts for 0.1-0.3% of the total mass of the lithium-rich manganese-based positive electrode material.
[0065] The appropriate mass ratio of organic carbon source can promote the mass transfer reaction, help form a stable spinel-like heterostructure on the surface of lithium-rich manganese-based core materials, and at the same time improve the electronic conductivity and electrochemical activity of the material surface, enhance the diffusion capacity of lithium ions, and effectively improve the first efficiency, rate performance and cycle stability of the battery through redox reactions on the lithium-rich surface; avoid insufficient carbon content, which is not conducive to decomposition and release to form a uniform carbon conductive layer; and is not conducive to the construction of certain oxygen vacancies; promote the formation of a complete and continuous spinel-like heterostructure layer between phosphate ions and the surface of lithium-rich manganese-based core materials; affect the electrochemical properties and structural stability of the preparation of lithium-rich manganese-based positive electrode materials.
[0066] As a further solution, the added amount of the composite coating layer of metal sulfide and metal boride accounts for 0.01-0.5% of the total mass of the lithium-rich manganese-based positive electrode material.
[0067] Furthermore, the stoichiometric ratio of the metal sulfide to the metal boride is selected from 1:(0.5-2).
[0068] As a further embodiment, the transition metal element is selected from one or more of iron, cobalt, manganese or nickel.
[0069] As a further solution, the raw materials of the nanocomposite phosphate carbon-containing coating layer include multivalent metal ion phosphate, a lithium source, and an organic carbon source.
[0070] As a further embodiment, the polyvalent metal ion is selected from Cu 2+ , Fe 2+ 、Co 2+ , Pb 2+ 、Zn 2+ , Mn 2+ 、Ni 2+ 、Al 3 + 、Ti 4+ or V 3+ One or more of .
[0071] Furthermore, the polyvalent metal ion is preferably selected from Fe 2+ .
[0072] As a further embodiment, the multivalent metal ion phosphate is selected from one or more of FePO4, Zn3(PO4)2, AlPO4, and Ti3(PO4)4.
[0073] Furthermore, the multivalent metal ion phosphate is preferably selected from FePO4.
[0074] As a further embodiment, the organic carbon source includes one or more of organic acids, sugars, and lipids.
[0075] The present invention selects an organic carbon source to decompose during the sintering preparation process to form a carbon material conductive layer when preparing a lithium-rich manganese-based positive electrode material. Compared with the use of an inorganic carbon source, it is more conducive to forming a uniform conductive network, thereby improving the conductivity and cycle stability of the material. In addition, the organic carbon source avoids the construction of oxygen vacancies with the lithium-rich manganese-based core material during the decomposition process, thereby improving the surface activity of the lithium-rich manganese-based core material. The decomposition process of the organic carbon source is an exothermic projection, which can further enhance the mass transfer effect and promote the formation of a spinel-like heterogeneous structure; the surface oxygen vacancies and the surface interface spinel-like structure enhance the material's cycle stability and rate performance, thereby effectively solving the problems existing in traditional lithium-rich manganese-based positive electrode materials.
[0076] Furthermore, the organic acid includes one or more of formic acid, acetic acid, propionic acid, lactic acid, butyric acid, acetic acid, oxalic acid, and citric acid.
[0077] Furthermore, the carbohydrate substance includes one or more of glucose, fructose, sucrose and maltose.
[0078] Furthermore, the lipid substances include one or more of fatty acids, triglycerides, phospholipids, and cholesterol.
[0079] As a further embodiment, the metal sulfide is selected from one or more of molybdenum sulfide, antimony sulfide and zirconium sulfide.
[0080] As a further embodiment, the metal boride is selected from one or more of titanium diboride and zirconium diboride.
[0081] In a second aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating, which is used to prepare the lithium-rich manganese-based positive electrode material described in the first aspect; the preparation method comprises the following steps performed in sequence: according to the stoichiometric ratio:
[0082] S1: Weighing a lithium-rich manganese-based precursor material, a lithium source, and a Q source, mixing them evenly, and then pre-sintering at a low temperature to obtain a doped lithium-rich manganese-based core material;
[0083] S2: Weigh a multivalent metal ion phosphate, a lithium source, an organic carbon source, and the doped lithium-rich manganese-based core material described in S1, mix them evenly, and perform a second sintering to obtain a lithium-rich manganese-based positive electrode material coated with a heterostructure surface;
[0084] S3: The lithium-rich manganese-based positive electrode material coated on the surface of the heterostructure described in S2 is evenly mixed with metal sulfide and metal boride, and subjected to a third sintering treatment to obtain a lithium-rich manganese-based positive electrode material compositely coated on the surface of the heterostructure.
[0085] When the preparation method is used to prepare the lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating as described in the first aspect, the lithium-rich manganese-based core material prepared by low-temperature pre-sintering has a low crystallinity, and then the second sintering is performed on the one hand to improve the crystallinity of the lithium-rich manganese-based core material to form a lithium-rich manganese-based core material with complete crystallinity, and on the other hand to induce mass transfer between the lithium-rich manganese-based core material and the multivalent metal ion phosphate contact interface to form a spinel-like heterogeneous structure layer; in addition, a lithium source is added during the second sintering process to supplement lithium; the outer layer of the phosphate coating layer is promoted to react with the supplemented lithium salt to form a LiG with a stable structure. a (PO4) b layer, effectively improving the rate and other electrochemical properties of lithium-rich manganese-based positive electrode materials. During the third sintering process, the structural stability of the material is further enhanced by adding metal sulfides and metal borides. At the same time, the side reactions between the electrolyte and the surface of the positive electrode material are suppressed, the loss of the electrolyte and the generation of by-products are reduced, thereby improving the cycle stability and overall performance of the battery. This preparation method is simple and efficient, which can ensure that the lithium-rich manganese-based positive electrode material has excellent electrochemical properties and structural stability and is suitable for large-scale production. By selecting the appropriate range of sintering time and temperature, it helps to avoid the inability to complete the mass transfer reaction due to too low temperature or too short reaction time, thereby affecting the formation of spinel-like heterostructures.
[0086] As a further solution, the added molar amount of the lithium source in S2 is the molar amount of the phosphate group of the multivalent metal ion phosphate in S2 minus (0.08-0.12)*the mass of the doped lithium-rich manganese-based core material in S1.
[0087] As a further embodiment, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium nitrate.
[0088] As a further solution, the lithium-rich manganese-based precursor material includes Ni a Co b Mn c (OH)2 and Ni a Co b Mn c CO3, wherein 0.28≤a≤0.42, 0≤b≤0.2, 0.6≤c≤0.7, a+b+c=1.
[0089] As a further embodiment, the Q source is selected from one or more of sodium carbonate, sodium hydroxide, sodium peroxide, sodium fluoride, magnesium fluoride, magnesium carbonate, magnesium hydroxide, and potassium carbonate.
[0090] As a further embodiment, the particle size of the multivalent metal ion phosphate is between 20 nm and 100 nm.
[0091] Multivalent metal phosphates of appropriate particle size help to achieve uniform coating on the surface of the material when mixed with the doped lithium-rich manganese-based core material, thereby accelerating the material transfer rate at the interface; this helps to accelerate the exchange and migration between phosphate ions and ions in the lithium-rich manganese-based material; and form a more uniform spinel-type heterostructure surface coating layer during the sintering process.
[0092] As a further solution, the low-temperature pre-sintering temperature is selected from 500 to 800° C., and the low-temperature pre-sintering time is selected from 1 to 5 hours.
[0093] Selecting an appropriate range of low-temperature pre-sintering treatment time helps to form a uniform lithium-rich manganese-based core material with appropriate crystallinity, thereby providing a good foundation for subsequent heterostructure surface coating. Too short a sintering time may lead to incomplete crystallization of the core material, while too long a sintering time may cause excessive sintering of the material, affecting its electrochemical properties. Therefore, by optimizing the temperature and time of low-temperature pre-sintering, the crystallization state of the core material can be effectively controlled, providing a good foundation for subsequent steps and ensuring that the final lithium-rich manganese-based positive electrode material has excellent electrochemical properties and structural stability.
[0094] As a further solution, the second sintering temperature is selected from 750° C. to 950° C., and the second sintering time is selected from 10 to 15 hours.
[0095] The second sintering temperature can further promote the improvement of the crystallinity of the lithium-rich manganese-based core material; at the same time, by coating the lithium-rich manganese-based core material with multivalent phosphates and organic carbon, the formation and stability of the spinel-like heterostructure layer and the diffusion rate of lithium ions in the material can be ensured at a suitable second sintering temperature. Too low a sintering temperature may not fully promote the crystallization and interfacial reaction of the material, while too high a temperature may cause the decomposition or structural damage of the material; thereby affecting the structural stability and conductivity of the lithium-rich manganese-based core material. Therefore, choosing a suitable second sintering temperature and time is crucial to optimizing the electrochemical properties of lithium-rich manganese-based positive electrode materials. In addition, by adding a lithium source to supplement lithium during the second sintering process, the lithium ions that may be lost during the low-temperature pre-sintering process can be effectively supplemented to ensure sufficient lithium ions in the final material. At the same time, the supplemented lithium ions can react with phosphates to generate electrochemically active materials, thereby further improving the electrochemical properties of the material.
[0096] As a further solution, the third sintering time is selected from 5 to 8 hours, and the third sintering temperature is selected from 400 to 600°C.
[0097] The present invention also uses metal borides and metal sulfides as the outermost layer of the lithium-rich manganese-based positive electrode material for coating; it is helpful to utilize the structural stability of metal sulfides and metal borides to further improve the conductivity and chemical stability of the material. The metal sulfide and metal boride as the outermost coating layer can effectively prevent the electrode material from directly contacting the electrolyte during the charging and discharging process, thereby reducing the occurrence of side reactions and improving the cycle life of the battery. In addition, the introduction of metal sulfides and metal borides can also enhance the mechanical strength of the material and reduce structural damage caused by volume changes during the charging and discharging process of the battery. By precisely controlling the temperature and time during the third sintering process, it can be ensured that the metal sulfide and metal boride are evenly covered on the surface of the lithium-rich manganese-based positive electrode material to form a protective layer, thereby improving the overall stability and safety of the material without reducing the electrochemical performance.
[0098] In the preparation method of the present invention, those skilled in the art can feed materials according to the stoichiometric ratio, that is, according to the proportional relationship between the elements of the lithium-rich manganese-based positive electrode material, and determine the corresponding stoichiometric ratio taking into account the losses during the feeding and preparation process.
[0099] In the third aspect, the present invention provides a lithium-manganese-rich positive electrode material with a heterogeneous structure surface composite coating as described in the first aspect, or a lithium-manganese-rich positive electrode plate, an electrode assembly, a battery cell, and an energy storage device with a heterogeneous structure surface composite coating obtained by the preparation method described in the second aspect.
[0100] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0101] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0102] Example 1
[0103] According to the stoichiometric ratio, 500 g of Ni 0.30 Co 0.01 Mn 0.69(OH)2 precursor material, 204g lithium carbonate, and 1.5g sodium carbonate are mixed in a ball mill at a mixing parameter of 300r / 2h. After mixing, the mixed material is placed in a sagger to be leveled and marked; the sagger is placed in a furnace for sintering at a sintering temperature of 600°C and a sintering time of 3h. The mixed material is taken out to preliminarily form a doped lithium-rich manganese-based core material, which is marked as blank D;
[0104] 8 g of FePO4, 1.5 g of lithium carbonate, and 2.0 g of citric acid were weighed and mixed evenly with 500 g of the blank D according to the stoichiometric ratio; the blank was kept at 800° C. for 12 h and then taken out to obtain a lithium-rich manganese-based positive electrode material coated with a heterogeneous structure, which was marked as material E;
[0105] According to the stoichiometric ratio, 300 g of material E, 0.5 g of molybdenum disulfide, and 0.5 g of titanium diboride were mixed evenly and sintered for the third time at 450° C. for 6 h to obtain a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating.
[0106] Example 2
[0107] The specific steps and methods are the same as those in Example 1, except that: 10 g of FePO4 is weighed.
[0108] Example 3
[0109] The specific steps and methods are the same as those in Example 1, except that 3.0 g of citric acid is used.
[0110] Example 4
[0111] The specific steps and methods are the same as those in Example 1, except that: 350 g of material E, 0.4 g of molybdenum disulfide, and 0.7 g of titanium diboride are taken.
[0112] Example 5
[0113] The specific steps and methods are the same as those in Example 1, except that the low-temperature pre-sintering is performed at 700° C. and the heat preservation time is 5 hours.
[0114] Example 6
[0115] The specific steps and methods are the same as those in Example 1, except that the secondary sintering is performed at 850° C. and the temperature is kept for 15 hours.
[0116] Comparative Example 1
[0117] The specific steps and methods are the same as those in Example 1, except that: 30 g of FePO4 is weighed.
[0118] Comparative Example 2
[0119] The specific steps and methods are the same as those in Example 1, except that no phosphate is added.
[0120] Comparative Example 3
[0121] The specific steps and methods are the same as those in Example 1, except that: 8 g of FePO4, 1.5 g of lithium carbonate, and 2.0 g of citric acid are weighed and mixed evenly with 500 g of the blank D according to the stoichiometric ratio; the blank is kept warm at 600°C for 8 h and the obtained lithium-rich manganese-based positive electrode material is marked as material E.
[0122] Comparative Example 4
[0123] The specific steps and methods are the same as those in Example 1, except that: 8 g of FePO4, 1.5 g of lithium carbonate, and 2.0 g of graphite are weighed and mixed evenly with the blank D500 g according to the stoichiometric ratio; the blank is kept at a high temperature of 800° C. for 12 h and then taken out to obtain a lithium-rich manganese-based positive electrode material, which is marked as material E;
[0124] Comparative Example 5
[0125] The specific steps and methods are the same as those in Example 1, except that: the third sintering coating of molybdenum disulfide and titanium diboride is not performed; 8g FePO4, 1.5g lithium carbonate, and 2.0g citric acid are weighed and mixed evenly with the blank D500g according to the stoichiometric ratio; the blank is kept warm at 800°C for 12h and then taken out to obtain a lithium-rich manganese-based positive electrode material.
[0126] Specific test methods and conditions:
[0127] Preparation of button battery: Preparation method: Mix the test sample: conductive agent SP: binder PVDF in a stoichiometric ratio of 90:5:5, add an appropriate amount of N-vinyl pyrrolidone as a solvent, mix them to form a uniform slurry, apply it on aluminum foil to make a positive electrode sheet, and prepare it into a positive electrode sheet after vacuum drying and roller pressing. Use metallic lithium as the negative electrode, use 1 mol / L lithium hexafluorophosphate (LiPF6) and a three-component mixed solvent of ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl potassium carbonate (EMC) = 1:1:1 (v / v) to form an electrolyte, use a polypropylene microporous membrane as a diaphragm, and assemble it into a CR2032 button battery in a glove box filled with inert gas.
[0128] Electrochemical performance test method: The buckle test adopts 25℃ normal temperature test, the first cycle test voltage is 2.5~4.8V, the nominal capacity is 250mAh / g, and the current density is 0.1C. This test method is used to calibrate the first cycle charge and discharge capacity and first efficiency of the material. During the cycle process, the test is carried out at 25℃ normal temperature, the first cycle test voltage is 2.5~4.6V, the nominal capacity is 250mAh / g, and the current density is 1.0C, which is used to calibrate the cycle performance and voltage decay performance of the material.
[0129] Table 1
[0130]
[0131] It can be seen from the data in Table 1 and the examples and comparative examples that Examples 1-6 have higher first-cycle coulombic efficiency and discharge specific capacity, while Comparative Examples 1-5 exhibit poor electrochemical performance. This shows that by optimizing the sintering temperature and time, adding an appropriate lithium source, and adjusting the coating type, the electrochemical performance of the lithium-rich manganese-based positive electrode material can be significantly improved; the structural stability and conductivity of the lithium-rich manganese-based positive electrode material are effectively improved, thereby enhancing the cycle life and overall performance of the battery.
[0132] It can be seen from the examples and comparative example 1 that when preparing a lithium-rich manganese-based positive electrode material, when the amount of phosphate added is too much compared to the example, the electrochemical performance decreases. This shows that the amount of phosphate added needs to be precisely controlled to ensure the integrity of the material structure. When the amount of phosphate added is too much, it is easy to cause the coating layer to be too thick, which affects the deintercalation of lithium ions, resulting in a low capacity of the lithium-rich manganese-based positive electrode material and poor cycle performance, which is not conducive to the improvement of its battery specific capacity and first-cycle coulomb efficiency during the charge and discharge cycle.
[0133] It can be seen from the embodiment and comparative example 2 that comparative example 2 does not add phosphate for coating relative to the embodiment; a stable spinel-like structure cannot be formed; this is because the metal ions and phosphate ions in the multivalent metal phosphate can provide the required charge balance; the phosphate easily interacts with the lithium-rich manganese-based core material in the chemical reaction; similar to the spinel-like structure, it is easy to form a spinel-like structure through mass transfer in the chemical reaction. Promote the improvement of the electrochemical performance of the battery.
[0134] It can be seen from the embodiment and comparative example 3 that the secondary sintering treatment time and temperature in comparative example 3 are lower than those in the embodiment, and the lithium-rich manganese-based positive electrode material prepared by the same has a lower discharge specific capacity and first-cycle coulomb efficiency during the battery cycle; this is because in the preparation method of the present invention, the lithium-rich manganese-based core material prepared by low-temperature pre-sintering has a low crystallinity, and then needs to be subjected to a second sintering treatment in a suitable temperature range, which, on the one hand, promotes the mass transfer of multivalent metal phosphates on the surface of the lithium-rich manganese-based core material, generates a spinel-like structure with good stability and lithium ion transmission path, and on the other hand, a suitable second sintering treatment also helps to promote the crystallinity of the lithium-rich manganese-based core material to form a lithium-rich manganese-based core material with complete crystallinity; therefore, when the second sintering treatment temperature and time used in comparative example 3 are too low, it is not conducive to the improvement of the crystallinity of the lithium-rich manganese-based core material and the generation of the spinel-like structure. As a result, the prepared lithium-rich manganese-based positive electrode material does not have good structural stability during the charge and discharge cycle of the battery; its electrochemical performance is also poor.
[0135] Compared with the embodiment, when comparative example 4 uses an inorganic carbon source for the second sintering and coating, it has a lower charge-discharge specific capacity and coulombic efficiency than the embodiment. This is because the organic carbon source used in the present invention can decompose and release oxygen vacancies during the sintering preparation process, providing more active sites; promoting the mass transfer between multivalent metal phosphate ions and the surface of the lithium-rich manganese-based core material to generate a stable spinel-like structure. On the other hand, the carbon material produced by decomposition helps to form a uniform carbon conductive layer, thereby greatly improving the electrochemical performance of the lithium-rich manganese-based positive electrode material.
[0136] It can also be seen from the embodiment and comparative example 5 that in comparative example 5, the outermost layer of the lithium-rich manganese-based positive electrode material is not coated with metal boride and metal sulfide, and it can be clearly seen that the first cycle coulomb efficiency is low during the charge and discharge cycle of the battery; this is because the presence of the outermost metal sulfide and metal boride helps to further enhance the structural stability of the lithium-rich manganese-based positive electrode material during the charge and discharge cycle, protecting the spinel structure from damage; and the presence of the outermost metal sulfide and metal boride has good interface stability; the stable protective layer can effectively block the corrosion of the electrolyte to the lithium-rich manganese-based positive electrode material and reduce the occurrence of side reactions. At the same time, they can also provide stable ion transmission channels and electron conduction paths, promote the transmission and balance of charges, and thus improve the performance and cycle life of the battery.
[0137] pass Figure 1 It can be seen that in the Raman spectrum test diagram of Example 1 of the present invention relative to Comparative Example 2, Example 1 has a -1 ~500cm -1 There are obvious spinel-like peaks in between.
[0138] pass Figure 2 It can be seen from the cycle comparison diagram of Example 1 and Comparative Example 5 that the cycle performance of Example 1 coated with metal boride and metal sulfide is better than that of Comparative Example 5, and the coated metal boride and metal sulfide reduce the side reactions at the interface.
[0139] pass Figure 3 It can be seen that the rate performance of the coated sample is significantly improved compared with the reference sample, and the 3C rate capacity retention rate of the material is increased from 64% to 68%, indicating that the coating scheme can effectively improve the rate performance of the material after forming a spinel-like structure.
[0140] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating, wherein the chemical formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)Li 1-y Q y TMO2@A / C@N; in, xLi2MnO3·(1-x)Li 1-y Q y TMO2 is a doped lithium-rich manganese-based core; 0<x<0.5, 0<y<0.1, Q is one or more of alkali metal elements or alkaline earth metal elements, TM is a transition metal element: A / C is a nanocomposite phosphate carbon-containing coating layer coated outside the inner core, A is a nanocomposite phosphate (LiG a (PO4) b ), G is a metal element of a multivalent metal ion, and C is a carbon material; N is a composite coating layer coated outside the nano-composite phosphate carbon-containing coating layer, and the composite coating layer contains metal sulfide and metal boride; wherein the contact interface between the nano-composite phosphate carbon-containing coating layer and the inner core is a spinel-type structure, and the remaining part is an olivine-type structure.
2. The lithium-rich manganese-based positive electrode material with a heterogeneous structure and composite coating according to claim 1, characterized in that: In Q, the alkali metal element is selected from one of sodium and potassium; the alkaline earth metal element is selected from magnesium; The transition metal element is selected from one or more of iron, cobalt, manganese or nickel; the multivalent metal ion is selected from Cu 2+ , Fe 2+ 、Co 2+ , Pb 2+ 、Zn 2+ , Mn 2+ 、Ni 2+ 、Al 3+ 、Ti 4+ or V 3+ One or more of; Furthermore, the polyvalent metal ion is preferably selected from Fe 2+ .
3. The lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating according to claim 1, characterized in that: The raw materials of the nanocomposite phosphate carbon-containing coating layer include multivalent metal ion phosphate, lithium source and organic carbon source; Further, the multivalent metal ion phosphate is selected from one or more of FePO4, Zn3(PO4)2, AlPO4, Ti3(PO4)4; Furthermore, the organic carbon source includes one or more of organic acids, sugars, and lipids; Furthermore, the multivalent metal ion phosphate is preferably selected from FePO4; Furthermore, the organic acid includes one or more of formic acid, acetic acid, propionic acid, lactic acid, butyric acid, acetic acid, oxalic acid, and citric acid; Furthermore, the sugar substance includes one or more of glucose, fructose, sucrose, and maltose; Furthermore, the lipid substances include one or more of fatty acids, triglycerides, phospholipids, and cholesterol.
4. The lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating according to claim 1, characterized in that: The metal sulfide is selected from one or more of molybdenum sulfide, antimony sulfide and zirconium sulfide; The metal boride is selected from one or more of titanium diboride and zirconium diboride.
5. The lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating according to claim 1, characterized in that: The ratio of the mass of Q to the total mass of the lithium-rich manganese-based positive electrode material is 0.01-0.3%; The nanocomposite phosphate (LiG a (PO4) b ), the mass of phosphate accounts for 0.7% to 1.5% of the total mass of the lithium-rich manganese-based positive electrode material; In the lithium-rich manganese-based positive electrode material with a composite coating on the surface of the heterogeneous structure, the molar ratio of phosphate to lithium is in the range of: PO4:Li=1:(0.6-1.3).
6. The lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating according to claim 1, characterized in that: The carbon content of the nanocomposite phosphate carbon-containing coating layer accounts for 0.1-0.3% of the total mass of the lithium-rich manganese-based positive electrode material; The addition amount of the composite coating layer of metal sulfide and metal boride accounts for 0.01-0.5% of the total mass of the lithium-rich manganese-based positive electrode material; Furthermore, the stoichiometric ratio of the metal sulfide to the metal boride is selected from 1:(0.5-2).
7. A method for preparing a lithium-rich manganese-based positive electrode material with a heterogeneous structure surface composite coating according to any one of claims 1 to 6, the method comprising the following steps performed in sequence: according to the stoichiometric ratio: S1: Weighing a lithium-rich manganese-based precursor material, a lithium source, and a Q source, mixing them evenly, and then pre-sintering at a low temperature to obtain a doped lithium-rich manganese-based core material; S2: Weigh a multivalent metal ion phosphate, a lithium source, an organic carbon source, and the doped lithium-rich manganese-based core material described in S1, mix them evenly, and perform a second sintering to obtain a lithium-rich manganese-based positive electrode material coated with a heterostructure surface; S3: The lithium-rich manganese-based positive electrode material coated on the surface of the heterostructure described in S2 is evenly mixed with metal sulfide and metal boride, and subjected to a third sintering treatment to obtain a lithium-rich manganese-based positive electrode material compositely coated on the surface of the heterostructure.
8. The preparation method according to claim 7, characterized in that: The lithium-rich manganese-based precursor material includes Ni a Co b Mn c (OH)2 and Ni a Co b MncCO3, 0.28≤a≤0.42, 0≤b≤0.2, 0.6≤c≤0.7, a+b+c=1; The Q source is selected from one or more of sodium carbonate, sodium hydroxide, sodium peroxide, sodium fluoride, magnesium fluoride, magnesium carbonate, magnesium hydroxide, and potassium carbonate; The lithium source is selected from one or more of lithium carbonate, lithium hydroxide and lithium nitrate; The added molar amount of the lithium source in S2 is the molar amount of the phosphate radical of the multivalent metal ion phosphate in S2 minus (0.08-0.12)*the mass of the doped lithium-rich manganese-based core material in S1; The particle size of the multivalent metal ion phosphate is between 20nm and 100nm.
9. The preparation method according to claim 7, characterized in that: The low-temperature pre-sintering temperature is selected from 500 to 800° C., and the low-temperature pre-sintering time is selected from 1 to 5 hours; The second sintering temperature is selected from 750°C to 950°C, and the second sintering time is selected from 10 to 15 hours; The third sintering temperature is selected from 400 to 600° C.; the third sintering time is selected from 5 to 8 hours.
10. A lithium-manganese-rich positive electrode material with a heterogeneous structure and a composite coating on the surface as described in any one of claims 1 to 6, or a lithium-manganese-rich positive electrode sheet with a heterogeneous structure and a composite coating on the surface obtained by the preparation method described in any one of claims 7 to 9, an electrode assembly, a battery cell, and an energy storage device.